2022
DOI: 10.1186/s12889-022-13330-6
|View full text |Cite
|
Sign up to set email alerts
|

Perceived cardiovascular disease risk and tailored communication strategies among rural and urban community dwellers in Rwanda: a qualitative study

Abstract: Background In Rwanda, cardiovascular diseases (CVDs) are the third leading cause of death, and hence constitute an important public health issue. Worldwide, most CVDs are due to lifestyle and preventable risk factors. Prevention interventions are based on risk factors for CVD risk, yet the outcome of such interventions might be limited by the lack of awareness or misconception of CVD risk. This study aimed to explore how rural and urban population groups in Rwanda perceive CVD risk and tailor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…The underestimation of CVD risk among community members was reported in previous studies conducted in other settings [12,27,28]. The misestimation of CVD risk among the community members was recorded in South Africa [25].The CVD risk underestimation recorded in the present study can be linked to poor understanding of the concept of CVD risk, which was reported among rural and urban community members in a previous study conducted in Rwanda [4]. Moreover, this poor understanding of CVD risk can be one of the contributors to low attendance at health facilities, as reported in a study conducted in South Africa [26].The low attendance at heath facilities observed in this study can also be explained by the low proportion of study participants who were very welling to attend a health facility for a medical check-up to rule out any heart disease.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…The underestimation of CVD risk among community members was reported in previous studies conducted in other settings [12,27,28]. The misestimation of CVD risk among the community members was recorded in South Africa [25].The CVD risk underestimation recorded in the present study can be linked to poor understanding of the concept of CVD risk, which was reported among rural and urban community members in a previous study conducted in Rwanda [4]. Moreover, this poor understanding of CVD risk can be one of the contributors to low attendance at health facilities, as reported in a study conducted in South Africa [26].The low attendance at heath facilities observed in this study can also be explained by the low proportion of study participants who were very welling to attend a health facility for a medical check-up to rule out any heart disease.…”
Section: Discussionsupporting
confidence: 51%
“…This study provided proof that CHWs can screen their fellow community members for (high) CVD risk, and community members accepted being screened by CHWs for (high) CVD risk in Rwanda. This is not surprising, since in one qualitative study recently conducted in Rwanda, community members expressed a need to be screened by CHWs for CVD risk [4]. A strong positive correlation between CVD risk scores measured by CHWs and CVD risk scores measured by nurses is proof that CHWs have the potential to conduct CVD risk screening using mobile-technology.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations